Risk factors of new vertebral compression fracture after percutaneous vertebroplasty or percutaneous kyphoplasty - Cheng, Yuanpei; Cheng, Xiaokang; Wu, Han (Frontiers in Endocrinology, 2022)
Background: New vertebral compression fracture (VCF) may occur in patients underwent percutaneous vertebroplasty (PVP) or percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fracture (OVCF). However, the risk factors of new VCF remain controversial. The research aimed to analyze the risk factors of new VCF after PVP or PKP. Methods: From August 2019 to March 2021, we retrospectively analyzed the patients preformed with PVP or PKP for OVCF at our institution. Age, gender, body mass index (BMI), smoking, drinking, hypertension, diabetes, fracture location, surgical method, hounsfield unit (HU) value, preoperative degree of anterior vertebral compression (DAVC), bisphosphonates, bone cement volume, bone cement leakage, and cement distribution were collected. The risk factors were obtained by univariate and multivariate analysis of the data. Results: A total of 247 patients were included in the study. There were 23 patients (9.3%) with new VCF after PVP or PKP. Univariate analysis showed that age (P < 0.001), BMI (P = 0.002), fracture location (P = 0.030) and a low HU value (P < 0.001) were significantly associated with new VCF after PVP or PKP. A low HU value was independent risk factor for new VCF after PVP or PKP obtained by multivariate regression analysis (OR = 0.963; 95% CI, 0.943-0.984, P = 0.001). Conclusions: In this study, a low HU value was an independent risk factor of new VCF after PVP or PKP.